VOCABULARY LEARNING THROUGH STUDENT-GENERATED GLOSSARIES IN EFL CLASSROOM - Niwayan Sukraini,; Pratika, Dellis; Cendikia Flory Aristia, (ENGLISH JOURNAL, 2025)
This study investigated vocabulary acquisition in an EFL classroom through student-generated glossaries, asking: which parts of speech students prefer, which semantic domains dominate, and how accurately and complexly students use target words in example sentences. Using purposive sampling, a descriptive content analysis was conducted on glossaries from three first-semester undergraduates. Entries and example sentences were coded in NVivo for part of speech, semantic domain, grammatical accuracy (error type), and sentence complexity; pilot coding and reliability checks informed the final codebook. Results showed nouns predominated (231 references), and high-frequency domains included idioms, people/relationships, technology, travel, and healthcare (390 references overall). Of 364 example sentences, simple sentences were most common (245), with complex (72), compound (38), and compound-complex (9) less frequent. Across sentences, 83 grammatical errors were identified, most often comma splices (10), missing verbs (9), and unclear meaning (9). These findings indicate learners' preference towards simple forms and struggle with clause boundary punctuation, verb form, and meaning clarity, underscoring the need for instruction that integrates form–meaning–use and sentence-level practice. Future research should enlarge the sample, examine proficiency and L1 effects, and test interventions that pair glossary building with guided example-sentence construction and feedback.